Ultra-long-term cycling stability of an integrated carbon–sulfur membrane with dual shuttle-inhibiting layers of graphene "nets" and a porous carbon skin. Issue 40 (1st May 2018) - Liu, Mingkai; Meng, Qinghua; Yang, Zhiyuan; Zhao, Xinsheng; Liu, Tianxi
Abstract : An integrated carbon–sulfur membrane (CSG/PC) with dual "shuttle-inhibiting" layers of graphene "nets" and a porous carbon (PC) skin can overcome the poor cycling performance of lithium–sulfur batteries. Abstract : An integrated carbon–sulfur (CSG/PC) membrane with dual shuttle-inhibiting layers was prepared by inserting graphene "nets" and a porous carbon (PC) skin, and the membrane achieved an extraordinary cycling stability up to 1000 cycles with an average Coulombic efficiency of ∼100%.